The burden and its determinants of mental health distress among adolescents dwelling in Africa: a systematic review and meta-analysis - Techilo Tinsae; Shegaye Shumet; Girmaw Medfu Takelle; Gidey Rtbey; Mamaru Melkam; Fantahun Andualem; Girum Nakie; Tesfaye Segon; Selam Koye; Setegn Fentahun; Wondale Getinet Alemu; Gebresilassie Tadesse (BMC, 2024)
Abstract Background Adolescent mental health issues are emerging as a significant public health concern across many low- and middle-income countries, particularly in Africa. This study aims to evaluate the aggregated prevalence and contributing risk factors of mental health distress among adolescents in Africa. Methodology A comprehensive search of PubMed, PsycINFO, Web of Science, Google Scholar, and HINARI databases was conducted to identify relevant articles on the prevalence and risk factors associated with mental health distress among African adolescents, published up to December 2023. The quality of the selected studies was assessed using the Newcastle-Ottawa Quality Assessment Scale. Heterogeneity among the studies was evaluated using the I² statistical test. Potential publication bias was assessed through a funnel plot and Egger's statistical test. This systematic review was registered with PROSPERO under reference number CRD42023494665. Results Eighteen studies encompassing data from 37,016 adolescents were included in the analysis. The overall prevalence of mental health distress among adolescents in Africa was found to be 27.34% (95% CI: 23.18-31.50). The occurrence of mental health distress is observed in older adolescents at a prevalence of 29.44% (95% CI: 23.26-35.66) and in younger adolescents at 24.73% (95% CI: 11.96-37.51). Significant risk factors identified included bullying victimization, with an odds ratio (POR) of 1.30 (95% CI: 1.16, 1.46), and experiencing hunger, with an odds ratio (POR) of 2.10 (95% CI: 1.13, 3.91). Conclusion The findings indicate a high prevalence of mental health distress among adolescents in Africa, highlighting the widespread impact on this demographic. These results underscore the urgent need for targeted interventions to prevent and address mental health distress among adolescents. Further research on a global scale is essential to develop effective prevention and treatment strategies tailored to this age group.